User verification through pointing characteristics: an exploration examination - Barrelle, Kate; Laverty, William; Henderson, Ron; Gough, Jon; Wagner, Michael; Hiron, Michael (International journal of human-computer studies, 1996)
Previous research has highlighted that all data security systems rest on the assumption of accurate user verification. Although much research has focused on speech and keystroke characteristics, no study has examined the potential of indirect cursor control devices, such as mouse or pen, as a means of personal user verification. This paper presents the result of an exploratory examination of the measurement of individual users' behaviour elicited while using two indirect input devices (puck and pen). Ten subjects undertook two series of 500 trials using the puck and pen in a counterbalanced design. Each trial involved guiding the cursor to one of ten possible targets, projected upon one of five angles of projection and one of two distances. Data recorded comprised a series of ( x, y) coordinates and associated time stamps of each component of the movement. Five parameters for each full movement were extracted-total time to reach the target, maximum velocity of the movement, maximum acceleration for the movement, time to maximum velocity of movement, time to maximum acceleration of the movement. Results of a series of Multivariate Analyses of Variance indicated that for both the puck and the pen data, there were statistically significant differences between subjects for each of the five parameters. This set of discriminating parameters was then embedded in a verification paradigm. Results indicated that the average error rates varied between 39% (S.D.=2%) and 14% (S.D.=2%) for the puck and 38% (S.D.=2%) and 12% (S.D.=2%) for the pen. Error rates were dependent upon the number of samples used when making the verification decision. This research suggests that pointing device measurements using the current parameters are not a viable method of user verification by themselves. However, with average error rates as low as 12%, it may be reasonable to integrate them into a multi-modal security system. Practical implications and future research directions are discussed.